Kejahatan Transnasional Perdagangan Ginjal di Kamboja Dalam Hukum Nasional dan Internasional - Naufal Muhamad Farghany; Syahrul Fauzul Kabir (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. Human organ trafficking is an illegal practice involving the sale, purchase, ortrade of human organs for commercial purposes. This practice violates human rights andhas serious impacts on victims and the integrity of the human body. Transnational crimescommitted by a kidney organ trafficking syndicate carried out by Indonesian citizens inCambodia who recruit and arrange the travel of victims are carried out by Indonesianpolice officers, including perpetrators of kidney organ trafficking originating from withinthe country and officers involved. This study aims to examine the trade in kidney organsfrom the perspective of national and international law as well as the systematics ofinternational cooperation between Indonesia and Cambodia in handling the transnationalcrime of selling kidney organs. The data collection method used in this research is thelibrary research method, namely the library data collection technique obtained throughlibrary research sourced from laws and regulations, books, official documents,publications, and research results relevant to the research topic. Research resultsindicate that the transnational crime of selling kidney organs violates both national andinternational laws. Indonesia and Cambodia have undertaken collaborative effortsthrough mutual legal assistance and an extradition treaty between ASEAN member states. Abstrak. Perdagangan organ manusia adalah praktik ilegal yang melibatkan penjualan,pembelian, atau perdagangan organ manusia untuk tujuan komersial. Praktik inimelanggar hak asasi manusia dan berdampak serius pada korban dan integritas tubuhmanusia. Kejahatan transnasional yang dilakukan oleh sindikat perdagangan organ ginjalyang dilakukan oleh warga negara Indonesia di Kamboja yang merekrut dan mengaturperjalanan korban dilakukan oleh petugas kepolisian Indonesia, termasuk pelakuperdagangan organ ginjal yang berasal dari dalam negeri dan petugas yang terlibat. Studiini bertujuan untuk meneliti perdagangan organ ginjal dari perspektif hukum nasional daninternasional serta sistematika kerja sama internasional antara Indonesia dan Kambojadalam menangani kejahatan transnasional penjualan organ ginjal. Metode pengumpulandata yang digunakan dalam penelitian ini adalah metode penelitian kepustakaan, yaituteknik pengumpulan data kepustakaan yang diperoleh melalui penelitian kepustakaanyang bersumber dari undang-undang dan peraturan, buku, dokumen resmi, publikasi, danhasil penelitian yang relevan dengan topik penelitian. Hasil penelitian menunjukkanbahwa kejahatan transnasional penjualan organ ginjal melanggar hukum nasional daninternasional. Indonesia dan Kamboja telah melakukan upaya kolaboratif melalui bantuanhukum timbal balik dan perjanjian ekstradisi antar negara anggota ASEAN.